2013
DOI: 10.5539/ies.v6n3p129
|View full text |Cite
|
Sign up to set email alerts
|

Faculty Members’ Ethical Behaviors: A Survey Based on Students' Perceptions at Universities in Turkey

Abstract: As members of academic team, faculty behaviors have vital influence on students' lives at universities. This study purposes to discover students' perceptions about faculty behaviors concerning their professional responsibilities, dating/sexual harassment, behaviors inside and behaviors outside the classroom and relationship based on self-interest. The study employs both a quantitative and a qualitative research technique. Results reveal that students' considerations are negative in terms of faculty behaviors i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
0
8
0
3
Order By: Relevance
“…Our results are consistent with some of the literature on the topic, indicating that sharing confidential information was considered unethical, with objectivity in interactions with students and during assessment regarded as essential. 7,8,12,13 The most prominent findings concerned clinical learning. Although clinical competency was considered essential to being a good teacher, most students considered admonishing or humiliating students in front of patients or other staff in clinical settings unethical.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results are consistent with some of the literature on the topic, indicating that sharing confidential information was considered unethical, with objectivity in interactions with students and during assessment regarded as essential. 7,8,12,13 The most prominent findings concerned clinical learning. Although clinical competency was considered essential to being a good teacher, most students considered admonishing or humiliating students in front of patients or other staff in clinical settings unethical.…”
Section: Discussionmentioning
confidence: 99%
“…3 Studies investigating faculty members perceptions in teacher-student interactions have indicated that teachers experience boundary dilemmas with respect to demonstrating a friendly, caring attitude while maintaining a healthy, productive level of control in the classroom, 4 and they consider intimate relationships, romantic propositions and sexually offensive conduct in faculty members unethical. 5 In contrast, studies examining students' perceptions of faculty members' unethical behaviour have shown that they considered certain behaviours towards students, including offering or accepting expensive gifts, lending or borrowing money, issuing invitations to dinner parties, 6 giving those who disagree lower grades, setting examinations that are inconsistent with course material, teaching without adequate preparation, sexual attraction 7 and sharing confidential information with colleagues 8 unethical. In a study examining medical students' ethical development, 9 students reported that clinicians' derogatory comments, made in either the presence or the absence of patients, were 'sometimes' or 'often' appropriate.…”
Section: Introductionmentioning
confidence: 99%
“…Etik; bireysel ve toplumsal ilişkilerin temelini oluşturan değerleri, normları, kuralları, kavramları ahlaksal açıdan araştıran, neyin yapılacağının ya da yapılmayacağının bilinmesini sağlayan, ahlaki bakımdan bir şeyin doğruyanlış ya da iyi-kötü olduğu hükmüne nasıl varılacağını gösteren, iyi / kötü, doğru / yanlış davranışların niteliğini ve dayanağını araştıran bir felsefe disiplinidir. 1,[3][4][5] Ayrıca etik, insanlar arasındaki iletişim ve eylem biçimlerini şekillendirmek ve iyileştirmek için belirlenen kurallar olarak kabul edilebilir. Bu açıdan bakıldığında, eylemleri ya da davranışları iyilik, dürüstlük, adalet, erdem ve suç gibi kavramlardan oluşan akılcı bir çerçeveden değerlendirmeye, eylemlere ya da davranışlara ilişkin ahlaki yargıların nasıl oluştuklarını çözümlemeye çalışır.…”
Section: Etik Nedir?unclassified
“…Bu açıdan bakıldığında, eylemleri ya da davranışları iyilik, dürüstlük, adalet, erdem ve suç gibi kavramlardan oluşan akılcı bir çerçeveden değerlendirmeye, eylemlere ya da davranışlara ilişkin ahlaki yargıların nasıl oluştuklarını çözümlemeye çalışır. 2,5 Akademik Etik, Meslek Etiği ve Meslek Ahlakı İdeal bir üniversitenin olmazsa olmazlarından biri kabul edilen ve ideal bir üniversitenin çekirdeğini oluşturan kavramlardan biri "akademik etik"dir. 1 Akademisyenlerin bilimsel çalışma ve akademik etkinlikleri sürecinde birikim ve bilgilerini paylaşma ve öğrencilerine aktarmada, bilimsel çalışmaların üretilmesi ve değerlendirilmesinde, iyi eğitilmiş bilim insanlarının yetiştirilmesi faaliyetlerinin her aşamasında etik davranış kurallarına uymayı ifade eder.…”
Section: Etik Nedir?unclassified
“…The most probable cheaters are those low in scholastic competence and high in subclinical psychopathic (Nathanson, 2010). The faculty ethical behaviours as fair assessment and clear information on applied rules are vital for students (Ozcan et al, 2013).…”
Section: Dependency Analysismentioning
confidence: 99%